Pathophysiological and Pharmaceutical Considerations for Enhancing the Control of Sarcoptes scabiei in Wombats Through Improved Transdermal Drug Delivery - Bains, Jaskaran; Carver, Scott; Hua, Susan (Frontiers in Veterinary Science, 2022)
Sarcoptic scabiei is an invasive parasitic mite that negatively impacts wombats, causing sarcoptic mange disease, characterized by alopecia, intense pruritus, hyperkeratosis, and eventual mortality. Evidence suggests that wombats may be unable to recovery from infection without the assistance of treatments. Transdermal drug delivery is considered the most ideal route of administration for in situ treatment in free-ranging wombats, as it is non-invasive and avoids the need to capture affected individuals. Although there are effective antiparasitic drugs available, an essential challenge is adequate administration of drugs and sufficient drug retention and absorption when delivered. This review will describe the implications of sarcoptic mange on the physiology of wombats as well as discuss the most widely used antiparasitic drugs to treat S. scabiei (ivermectin, moxidectin, and fluralaner). The prospects for improved absorption of these drugs will be addressed in the context of pathophysiological and pharmaceutical considerations influencing transdermal drug delivery in wombats with sarcoptic mange.